Challenges of Implementing Augmentative Alternative Communication (AAC) Technology in Multiple Disabilities After School Graduation: A Parent's Experience - Trustisari, Hastin (IJER (Indonesian Journal of Educational Research), 2023)
Augmentative alternative communication (AAC) is an important component for people with multiple disabilities who have communication barriers. Many studies have focused on the implementation of AAC in the classroom but limited outside of school. This study aims to describe parents' experiences of assisting their multiple disabilities with visual impairment (MDVI) children to use AAC at home after school. This study used a qualitative ethnographic approach involving 6 parents of MDVI children with complex communication needs. The researcher conducted in-depth interviews, observations, and documentation studies. Thematic analysis using the manual data analysis procedure (MDAP) was applied in this study. 5 central themes were found in this study including parents' paradigm, acceptance, challenges, concerns, and expectations on the use of AAC at home. Furthermore, this study recommends further studies on member involvement to support communication independence through AAC for multiple disabilities post-graduation.